2018
DOI: 10.1111/jeb.13303
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for lower plasticity in CTMAX at warmer developmental temperatures

Abstract: Understanding the capacity for different species to reduce their susceptibility to climate change via phenotypic plasticity is essential for accurately predicting species extinction risk. The climatic variability hypothesis suggests that spatial and temporal variation in climatic variables should select for more plastic phenotypes. However, empirical support for this hypothesis is limited. Here, we examine the capacity for ten Drosophila species to increase their critical thermal maxima (CT ) through developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 68 publications
3
24
0
Order By: Relevance
“…Accordingly, we do not find any support suggesting that temperate species have higher plasticity than tropical species. Our finding of similar plasticity among species from the temperate and tropical origin is also consistent with earlier reports from Drosophila [34,37,55,56] and is emerging as a general pattern in ectothermic animals [35], although some have found a weak but positive association between plasticity and latitude in a large meta-analysis of ectotherms [36]. Thus, we conclude that our empirical findings offer no support for the idea that distance from the equator, degree of seasonality or thermal safety margin (calculated as the difference between upper thermal limit and maximum environmental temperature) correlate with the degree of plasticity, as has been suggested elsewhere [12,13,57].…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, we do not find any support suggesting that temperate species have higher plasticity than tropical species. Our finding of similar plasticity among species from the temperate and tropical origin is also consistent with earlier reports from Drosophila [34,37,55,56] and is emerging as a general pattern in ectothermic animals [35], although some have found a weak but positive association between plasticity and latitude in a large meta-analysis of ectotherms [36]. Thus, we conclude that our empirical findings offer no support for the idea that distance from the equator, degree of seasonality or thermal safety margin (calculated as the difference between upper thermal limit and maximum environmental temperature) correlate with the degree of plasticity, as has been suggested elsewhere [12,13,57].…”
Section: Discussionsupporting
confidence: 93%
“…Another important finding of our study is that workers from intermediate-elevation populations (1,000 and 1,300 m), who experienced the greatest temperature variability, displayed significantly greater thermal tolerance (had higher LT50 values) than workers from lower and higher elevation populations. These results support the CVH, which posits that exposure to greater temperature variability selects for greater thermal tolerance (Baudier, D'Amelio, Malhotra, O'Connor, & O'Donnell, 2018;Chan et al, 2016) or for more plastic phenotypes (Kellermann & Sgrò, 2018). Different recent studies have also found support for the CVH in a variety of organisms: tropical tadpoles (Gutiérrez-Pesquera et al, 2016); Andean frogs (Pintanel, Tejedo, Ron, Llorente, & Merino-Viteri, 2019); snails and vascular plants in the Caucasus (Mumladze, Asanidze, Walther, & Hausdorf, 2017); tropical aquatic insects (Shah et al, 2017); and tropical army ants (Baudier et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…Current evidence suggests that plastic responses of insects to heat are limited and may not be sufficient to withstand ongoing warming trends (Gunderson & Stillman, ; Kellermann & Sgrò, ). Furthermore, although important for rapid responses to sudden climate changes, plasticity has not yet been linked to sustained responses with fitness benefits across generations in insects (Kellermann & van Heerwaarden, ; Radchuk et al ., ).…”
Section: Coping With High Temperatures: Plastic and Evolutionary Respmentioning
confidence: 99%